Conhecimento especializado de licenciandos de Matemática mobilizado em ação formativa sobre geometria espacial - Mauso, Ana Paula Truzzi (2023)
This research aimed to analyse the specialized mathematical knowledge of mathematics undergraduate students in the distance learning modality of the Federal Institute of Education, Science and Technology of Mato Grosso (IFMT), at the Bela Vista Campus, during a formative action involving spatial geometry, more specifically, the subject of prisms, pyramids, and their relations. The data were collected virtually during a ten-hour formative action synchronous and asynchronous meetings, between March and April, in 2022. The research follows the interpretative paradigm, being exploratory in nature, with an interpretative focus and a qualitative methodological approach. The analysis of the specialised knowledge that participants in their initial mathematics teaching training used in the formative action included systematic comparisons between the units of analysis (excerpts from the transcripts), the definitions of the MTSK categories and subdomains and the theoretical lens of textual discourse analysis. The research identified MTSK domains and subdomains in several moments of the formative action, with a greater presence of Knowledge of Topics and a lesser presence of Knowledge of the Structure of Mathematics, leading us to propose guidelines to strengthen the initial formation of mathematics teachers related to spatial geometry.